Maine’s 2018 Election: Bonds Continue to Hold - Melcher, James (Maine Policy Review, 2019)
This commentary follows up on Melcher’s article on bond issues from 2016, and it finds that these and other past tendencies in Maine bond voting held true once again in 2018.
Keywords: bond; referenda; transportation bonds; education bonds